Simultaneous Determination of Ferulic Acid and Vanillin in Vanilla Extracts Using Voltammetric Sensor Based on Electropolymerized Bromocresol Purple - Guzel Ziyatdinova; Anastasiya Zhupanova; Rustam Davletshin (Sensors, 2021)
Natural phenolic antioxidants are one of the widely studied compounds in life sciences due to their important role in oxidative stress prevention and repair. The structural similarity of these antioxidants and their simultaneous presence in the plant samples stipulate the development of methods for their quantification. The current work deals with the simultaneous determination of vanillin and its bioprecursor ferulic acid using a voltammetric sensor for the first time. A sensor based on the layer-by-layer deposition of the polyaminobenzene sulfonic acid functionalized single-walled carbon nanotubes (f-SWCNTs) and electropolymerized bromocresol purple has been developed for this purpose. The best response of co-existing target analytes was registered for the polymer obtained from the 25 µM dye by 10-fold potential cycling from 0.0 to 1.2 V with the scan rate of 100 mV s−1 in 0.1 M phosphate buffer (PB), pH 7.0. Scanning electron microscopy (SEM), cyclic voltammetry and electrochemical impedance spectroscopy (EIS) confirmed the effectivity of the sensor developed. The linear dynamic ranges of 0.10–5.0 µM and 5.0–25 µM for both analytes with the detection limits of 72 nM and 64 nM for ferulic acid and vanillin, respectively, were achieved in differential pulse mode. The sensor was applied for the analysis of vanilla extracts.